PENGARUH PENGGUNAAN MEDIA BIG BOOK TERHADAP KEMAMPUAN LITERASI MEMBACA SISWA KELAS II MI DI KOTA LHOKSEUMAWE - Yuliana; Rosimanidar; Novi Diana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Reading literacy is a foundational skill that plays an essential role in supporting students’ academic development at the elementary school level. However, initial observations in second-grade students at Madrasah Ibtidaiyah in Lhokseumawe City indicated that their reading literacy skills were still relatively low. These difficulties were seen in students’ limited fluency in reading, low comprehension of text content, inability to draw simple conclusions, and lack of responsiveness during reading activities. One instructional strategy that can be used to address this issue is the implementation of Big Book media, which presents reading materials in large formats accompanied by attractive illustrations to enhance students’ attention, motivation, and understanding. This study aimed to analyze the effect of Big Book media on students’ reading literacy skills in Indonesian language learning. The research used a quantitative approach with an experimental design involving a control and experimental group. The population consisted of 50 second-grade students of MIS Banda Masen Lhokseumawe, with 25 students assigned to each group. Data were collected using oral tests in the form of pretest and posttest. The data were analyzed using normality and homogeneity tests, followed by hypothesis testing using the Independent Sample t-Test. The results showed an improvement in the experimental class with a posttest mean score of 87.32 compared to the control class with 77.60. The statistical test resulted in a t-value of 4.148 with a significance value of 0.000 < 0.05, indicating that Big Book media had a significant effect on improving students’ reading literacy skills. In conclusion, the use of Big Book media is effective in enhancing students’ reading literacy by increasing reading interest, comprehension, and learning engagement. Keywords: Big Book, reading literacy, elementary students.